2020
DOI: 10.1177/2382120520968072
|View full text |Cite
|
Sign up to set email alerts
|

Shared Living Experiences by Physicians have a Positive Impact on Mental Health Attitudes and Stigma among Medical Students: A Mixed-Methods Study

Abstract: Introduction: Medical culture can make trainees feel like there is neither room for mistakes, nor space for personal shortcomings in the makeup of physicians. A dearth of role models who can exemplify that it is acceptable to need support compounds barriers to help-seeking once students struggle. We conducted a mixed-methods study to assess the impact of physicians sharing their living experiences with medical students. Methods: Second-year medical students participated, through synchronized videoconferencing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…With regards to the use of E-contact to reduce stigma toward mental disorders, to date, only one experimental study has been conducted, and has demonstrated that E-contact reduces anxiety, rage and stereotypes toward individuals with schizophrenia ( 38 ). In that sense, this confirms the relevance of including E-contact in interventions aimed at reducing stigma toward people with mental disorders, for instance through the use of synchronous videoconferencing ( 61 ).…”
Section: Introductionsupporting
confidence: 69%
“…With regards to the use of E-contact to reduce stigma toward mental disorders, to date, only one experimental study has been conducted, and has demonstrated that E-contact reduces anxiety, rage and stereotypes toward individuals with schizophrenia ( 38 ). In that sense, this confirms the relevance of including E-contact in interventions aimed at reducing stigma toward people with mental disorders, for instance through the use of synchronous videoconferencing ( 61 ).…”
Section: Introductionsupporting
confidence: 69%
“…At the professional level, the emphasis shifts from a culture of wellness to a culture of vulnerability 132,133 and self-compassion, 134 which acknowledges that physicians are not perfect, that they will make mistakes, 30 and that they need to be vulnerable and support one another. 135,136 Physicians recognize and acknowledge that they may have an Achilles' heel as it pertains to perfectionism and self-criticism and dedicate themselves to developing skills to address these mindsets.…”
Section: The Past: the Era Of Distressmentioning
confidence: 99%
“…Advances in Medical Education and Practice 2021:12 1384 we demonstrated reductions in depression-related stigma after exposure to two psychiatrists (one senior, one midcareer) sharing openly their symptoms, treatment, recovery, and ongoing adjustment to their living (rather than lived) experiences. 35 We replicated this finding twice: one in a second cohort of medical students in the same school, 36 and another in a multisite cohort of physician assistants, 37 in which the sharing, critically, was undertaken by senior physician assistants, ie, members of the same profession.…”
Section: Dovepressmentioning
confidence: 74%